2018
DOI: 10.3390/foods7040049
|View full text |Cite
|
Sign up to set email alerts
|

Betaine in Cereal Grains and Grain-Based Products

Abstract: Betaine is a non-essential nutrient which performs several important physiological functions in organisms. Abundant data exist to suggest that betaine has a potential for prevention of chronic diseases and that its dietary intake may contribute to overall health enhancement. Several studies have pointed out that the betaine status of the general population is inadequate and have suggested nutritional strategies to improve dietary intake of betaine. Cereal-based food has been implicated as the major source of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Additionally, choline is a precursor of the gut bacteria-derived metabolites, trimethylamine N-oxide [13]. Betaine is a bioactive compound that can spare some of choline's actions and is found in wheat bran, wheat germ, and spinach, thereby making it a useful food for pregnant women who are vegetarian or vegan [14][15][16].…”
Section: Functionsmentioning
confidence: 99%
“…Additionally, choline is a precursor of the gut bacteria-derived metabolites, trimethylamine N-oxide [13]. Betaine is a bioactive compound that can spare some of choline's actions and is found in wheat bran, wheat germ, and spinach, thereby making it a useful food for pregnant women who are vegetarian or vegan [14][15][16].…”
Section: Functionsmentioning
confidence: 99%
“…In general, wheat grains have been considered a primary source of energy (carbohydrates), proteins, vitamins and minerals (especially micronutrients, such as iron and zinc) in human diets [2,3,[6][7][8][9][10]. Indeed, the potential benefits of wheat on human health are well known and have been extensively studied [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In general, wheat grains have been considered a primary source of energy (carbohydrates), proteins, vitamins and minerals (especially micronutrients, such as iron and zinc) in human diets [2,3,[6][7][8][9][10]. Indeed, the potential benefits of wheat on human health are well known and have been extensively studied [6,[11][12][13]. Besides the major components, several phytochemicals conferring antioxidant properties [14][15][16][17] and dietary fibers contribute to reduce the risks for cardiovascular disease and colon cancers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although betaine is known as a nonessential nutrient, numerous studies in recent years reported a wide range of its health benefits (Filip cev, Koji c, Krulj, Bodroža-Solarov, & Ili c, 2018). For that reason betaine is used as dietary supplement and as functional ingredient (Filip cev et al, 2016).…”
Section: Introductionmentioning
confidence: 99%